1990
DOI: 10.1093/jn/120.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Viscous Indigestible Polysaccharides on Pancreatic-Biliary Secretion and Digestive Organs in Rats

Abstract: Effects of viscous indigestible polysaccharides on the pancreas exocrine function were investigated in growing rats. Rats were fed a nonfiber diet or a diet containing approximately 5% of one of the following fibers: apple pectin, lambda-carrageenan, locust bean gum, gum xanthan, guar gum or sodium (Na) alginate. Pancreatic-bile secretion was found to be elevated in rats fed for 2 wk the highly viscous polysaccharides, sodium alginate, locust bean gum, gum xanthan and guar gum. The polysaccharides may have int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
111
4
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(132 citation statements)
references
References 26 publications
13
111
4
4
Order By: Relevance
“…Ide et al (1989) and Ikegami et al (1990) affirmed that the nonstarch polysaccharides can influence the lipid metabolism because viscosity can increase the secretion of bile, and consequently result in loss of those acids in feces. Results from this study do not agree with Edney et al (1989), who observed worse results for fecal digestibility of fat in rats and an increase in IV in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Ide et al (1989) and Ikegami et al (1990) affirmed that the nonstarch polysaccharides can influence the lipid metabolism because viscosity can increase the secretion of bile, and consequently result in loss of those acids in feces. Results from this study do not agree with Edney et al (1989), who observed worse results for fecal digestibility of fat in rats and an increase in IV in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NDF and its lignin fraction in particular have a high water retention capacity and thereby increase the viscosity of the digesta, which slows mass transfer and enzymatic reactions, and hence digestion and absorption of nutrients (Buraczewska et al, 2007). Furthermore, gastric, pancreatic and biliary secretions appear to increase with NDF content of the feed (Ikegami et al, 1990), which would increase endogenous losses of protein due to sloughing of intestinal epithelium (Shah et al, 1982) in addition to digestive proteases. SID is estimated from the AID and adjusted for basal endogenous AA contributions, therefore including specific endogenous losses.…”
Section: Prediction Of Standardized Ileal Digestibility Of Essential mentioning
confidence: 99%
“…Apple pulp processing and juice manufacturing is now a booming industry and recently apple products are identified with cholesterol lowering property [12,14,15,16]. The dietary fiber content in apple further adds up the double benefit of cholesterol lowering with renal dysfunction and enhanced fecal steroid excretion [12,14,15,16]. Lithogenic diets are advocated as inducing cholesterol saturation due to their action on cholesterol sterol to make cholesterol free as one of the major lithogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The cholesterol lowering diets rich in omega 3 and omega 6 fatty acids have been investigated and reported to show major benefit in lipid lowering including cholesterol lowering [25]. The diets rich in fibers have been a major attention since last decade due to their double benefit to reduce lipids with cholesterol desaturation in the body and maintaining intestinal satiety free from any microvillus membrane damage [11,12,13,14,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation